Synthesis of a Library of 1,5,2-Dithiazepine 1,1-Dioxides. Part 2: Routes to Bicyclic Sultams - Zang, Qin (2012)
The synthesis of a library of bicyclic sultams incorporating the 1,5,2-dithiazepine 1,1-dioxide moiety is reported. Following scaffold synthesis via a one-pot sulfonylation/intramolecular thia-Michael protocol, several additional cyclization strategies have been realized enabling access to new bicyclic sultams.